Cardiac implantable electronic device infection in the cardiac referral center in Thailand: incidence, microbiology, risk factors, and outcomes. Issue 6 (27th September 2018) - Korkerdsup, Theerawat; Ngarmukos, Tachapong; Sungkanuparph, Somnuek; Phuphuakrat, Angsana
Abstract: Background: Despite the long experience of cardiac implantable electronic device (CIED) implantation in Thailand, epidemiology of CIED infection in Thailand has never been studied. Methods: A retrospective cohort study was conducted at the cardiac referral center in Thailand to investigate incidence of CIED infection and causative organisms between October 2002 and December 2017. A matched case‐control study was performed to determine the factors associated with CIED infection. Results: Incidence of CIED infection was 0.9% with a stable trend during the studied period. There were 54 episodes of CIED infection. The median (interquartile range) age of the patients was 67.5 (53.0‐75.0) years. A total of 29 (53.7%), 18 (33.3%), and 7 (13.0%) were permanent pacemaker, automatic implantable cardioverter‐defibrillator, and cardio‐resynchronization therapy‐related infection, respectively. Gram‐positive cocci were the most common organism (24 episodes, 44.4%). Gram‐negative bacilli were isolated in six episodes (11.1%). About 9.3% were polymicrobial and 35.2% were culture negative. Multivariate analysis showed that previous CIED infection and generator revision procedure were associated with CIED infection (odds ratio [OR] 48.56, 95% confidence interval [CI] 3.72‐633.62; P = 0.003 and OR 19.99, 95% CI 1.28‐333.24; P = 0.033 respectively). Forty (74.1%) cases were cured. Leaving device in situ was the only factor significantly associated with poor outcome (OR 11.40, 95% CI 1.52‐85.73; P = 0.018). Conclusions: In Thailand, while CIED implantation is rising, incidence of CIED infection is stable. Microbiology of CIED infection in Thailand is similar to western countries, albeit a higher proportion of negative culture. Previous CIED infection and generator revision procedure are associated with CIED infection.